Role-imposition or role-improvisation - some theoretical principles - Powers, C (Economic & Social Studies, 1981)
Two assumptions are made. First, role-improvisation and structural determination of role content are viewed as opposing processes inherent in all situations. Second, the relative importance of these processes is assumed to differ from case to case. Conditions effecting outcomes of the opposition between role-improvisation and imposition are specified in a series of theoretical principles. These principles constitute boundary conditions linking interactionist and structural perspectives.
Keywords: Economics; Sociology